Mathematics teachers’ perception of lesson study as a continuous professional development programme - Suhaili, Ade Shahren; Khalid, Madihah (SEAMO REgional Centre for Education, 2011)
Lesson Study can be viewed as a continuous development programme because it offers teachers support in an environment unlike other traditional continuous development programmes. In this study, 28 primary mathematics teachers were surveyed and 4 out of the 28 were interviewed to examine how they perceived Lesson Study as professional development. Data were also obtained from reflective journal of four of the teachers. Three themes related to the positive aspect of teachers’ perceptions of Lesson Study as a professional development and the journals of the teachers suggests the following: Lesson Study promotes the practice of teaching innovatively; Lesson Study provides teachers with a platform to improve and reflect their own teaching; Lesson Study has many advantages compared to other professional development programmes.